Microvesicles as Emerging Biomarkers and Therapeutic Targets in Cardiometabolic Diseases - Chen, Yan (Genomics Proteomics Bioinformatics, 2018)
Microvesicles (MVs, also known as microparticles) are small vesicles that originate from plasma membrane of almost all eukaryotic cells during apoptosis or activation. MVs can serve as extracellular vehicles to transport bioactive molecules from their parental cells to recipient target cells, thereby serving as novel mediators for intercellular communication. Importantly, more and more evidence indicates that MVs could play important roles in early pathogenesis and subsequent progression of cardiovascular and metabolic diseases. Elevated plasma concentrations of MVs, originating from red blood cells, leukocytes, platelets, or other organs and tissues, have been reported in various cardiometabolic diseases. Circulating MVs could serve as potential biomarkers for disease diagnosis or therapeutic monitoring. In this review, we summarized recently-published studies in the field and discussed the role of MVs in the pathogenesis of cardiometabolic diseases. The emerging values of MVs that serve as biomarker for non-invasive diagnosis and prognosis, as well as their roles as novel therapeutic targets in cardiometabolic diseases, were also described.